2019
DOI: 10.4251/wjgo.v11.i12.1172
|View full text |Cite
|
Sign up to set email alerts
|

Difference in failure patterns of pT3-4N0-3M0 esophageal cancer treated by surgery vs surgery plus radiotherapy

Abstract: BACKGROUNDThere has been no study comparing the difference in the failure patterns between patients with or without postoperative radiotherapy (PORT) after esophagectomy for pT3-4N0-3M0 esophageal squamous cell carcinoma (ESCC).AIMTo investigate the difference in the failure patterns of stage pT3-4N0-3M0 ESCC patients with or without PORT.METHODSPatients with stage pT3-4N0-3M0 ESCC, who underwent surgery with or without PORT, were enrolled in this study. The primary endpoint was to investigate the difference i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Chen et al [ 20 ] found that PORT was also associated with lower recurrence rates in patients with tumors in the supraclavicular and upper- and middle-mediastinal regions. Zeng et al [ 29 ] found that PORT reduced the LR from 92.0% to 35.7% in patients with TNM stage II/III ESCC. A systemic review by Liu et al [ 23 ] concluded that PORT clearly reduced the risk of LR in patients with ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al [ 20 ] found that PORT was also associated with lower recurrence rates in patients with tumors in the supraclavicular and upper- and middle-mediastinal regions. Zeng et al [ 29 ] found that PORT reduced the LR from 92.0% to 35.7% in patients with TNM stage II/III ESCC. A systemic review by Liu et al [ 23 ] concluded that PORT clearly reduced the risk of LR in patients with ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Ni et al [ 9 ], PORT decreased the absolute local regional recurrence rate by 20.0%. Zeng et al [ 32 ] showed that PORT significantly reduced LR from 92.0% to 35.7%; however, DM increased from 19.0% to 75.0%. However, in the study by Li et al [ 10 ] local recurrence rates in patients with II-III ESCC were similar among the SA, PORT, and POCRT groups ( P =0.10); the POCRT group had significantly fewer cases of hematogenous metastasis and overall recurrence.…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 5 , 7 , 15 , 19 However, according to many retrospective studies, the recurrence rate of the tumor bed is very low in patients with EC after radical surgery, 50 even in patients with pT3-4 stages. 55 , 56 The recurrence rate of the anastomotic site is usually less than 5.0% (2.8–8.7%). 10 , 12 , 57–59 To these points, these sites may not be necessary in the clinical target volume (CTV) of PORT for thoracic EC.…”
Section: Controversies Of Clinical Issuesmentioning
confidence: 99%